Electric and magnetic field measurements for high voltage transmission lines - Zeki Çelik, Mehmet (JET on-line, 2019)
A power system is a facility that creates low-frequency electromagnetic fields (EMF) with its highvoltage level and high electric current capacity. In this respect, these electromagnetic fields need to be significantly evaluated from the aspects of both those who are exposed to the fields due to the structure of the facility during their daily lives and those who are exposed to the fields due to their occupation. In this study, the transmission lines and substations in the power system of Turkey are evaluated on account of electric and magnetic field measurements. Firstly, the people living in general public zones near the transmission line or substation were examined. In another part of the study, measurements were made in the occupational exposure of the staff in the energy zone. The results obtained from measurements are compared with the limit values provided by the International Commission on Non%Ionizing Radiation Protection (ICNIRP). The measurements were performed by NARDA EFA-300 electromagnetic field measurement. The closest point to the ground was determined as the reference point for the measurements performed on transmission lines. The results for different distances were obtained by performing measurements following those reference points with fixed distances.
Keywords: electric field; electromagnetic filed; elektroenergetski sistem; ELF; ICNIRP; magnetic field; nizkofrekvenčna elektromagnetna polja